2012
DOI: 10.5005/jp-journals-10006-1181
|View full text |Cite
|
Sign up to set email alerts
|

Why Obstetric Patients are admitted to Intensive Care Unit? A Retrospective Study

Abstract: Pregnant women are often young and in their reproductive years. In majority of them, pregnancy and labor usually progresses uneventfully. Sudden complications occurring during this period may lead to maternal mortality. Though obstetric admission forms a small proportion of ICU admission, mortality among them is high. Proper antenatal care is still the mainstay of preventing complications in pregnant woman. This study was conducted to evaluate the obstetric admission to intensive care unit and causes and outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 5 publications
3
7
1
Order By: Relevance
“…Mean age of patients in our study was 25.4 years which is comparable to another Indian study (Ghike S et al 2012). 62 %( 31 out of 50 patients) requiring obstetric critical care were referrals from peripheral units to our tertiary care centre which is similar to 61.8% of another study (Bhadade et al2012).…”
Section: Discussionsupporting
confidence: 86%
“…Mean age of patients in our study was 25.4 years which is comparable to another Indian study (Ghike S et al 2012). 62 %( 31 out of 50 patients) requiring obstetric critical care were referrals from peripheral units to our tertiary care centre which is similar to 61.8% of another study (Bhadade et al2012).…”
Section: Discussionsupporting
confidence: 86%
“…This is comparable to the rate of 0.4%-2.4% reported by other authors (2-6). The mean age of patients and gestational age at the time of hospitalization were similar to previous studies (2,4,7). Pregnancy-induced hypertension is a common cause of maternal morbidity and mortality, especially in developing countries (2,7-10).…”
Section: Discussionsupporting
confidence: 86%
“…The observed rate is rather very low in comparison to most of the studies. 5,12,13 Major cause of mortality in our patients was haemorrhage and majority presented in decompensated state, thus reflecting the lack of well-equipped maternal care. Authors observed a higher caesarean delivery rate (50.7%) in the ICU cohort.…”
Section: Discussionmentioning
confidence: 88%